Epilepsy and Self-Management - OĞUZ, SIDIKA (KARE PUBL, 2016)
Epilepsy is a chronic disease. A high quality of life can be achieved when seizures are controlled, requiring important behavioral and psychosocial adjustments. Treatment and care involves self-management as well as medical intervention, including adherence to healthy behavior and other means of controlling seizure, in order to ensure a high quality of life. Effective self-management programs should take an educational approach that encourages self-sufficiency, focuses on the establishment of environmental support, determines consistent strategies for care, and instructs patients in self-evaluation. Self-management is more effective when patients are trained and self-sufficient, requiring the participation of expert nurses as educators. The objective of the present article was to draw attention to the importance of self-management in patients living with epilepsy.
Keywords: Epilepsy; nursing; self-sufficiency; self-management; ADULTS; EDUCATION; EFFICACY; STIGMA; PEOPLE; LIFE; CARE; PREDICTORS; ADHERENCE; BEHAVIORS